NON-CLASSIC FORM OF CONGENITAL ADRENAL HYPERPLASIA - Miolski, Jelena; Ješić, Maja; Bojić, Vladislav; Kovačević, Smiljka; Blagojević, Jelena; Didić, Nevena; Zdravković, Vera (Medical Research, 2023)
Introduction: Congenital adrenal hyperplasia is an autosomal recessive disease caused by gene mutation resulting in 21α-hydroxylase deficiency and a consequent reduction in adrenal steroidogenesis. The disease could present as classical and non-classic form. The frequency of the non-classic form is 0.1% in the general population, the most common clinical presentation is premature adrenarche, and the diagnosis is made by determining the concentration of 17-hydroxyprogesterone. The recommended treatment is hydrocortisone with close monitoring of the growth. Case report: A 7.5-year-old girl was admitted due to premature puberty, accelerated bone maturation and tall stature. The clinical exam revealed hypertrichosis, normal blood pressure and normal genital ultrasound. The karyotype was 46 XX, the basal and stimulated levels of 17-hydroxyprogesterone were elevated. Clinical and laboratory regression with stagnation of bone and body growth after starting treatment with hydrocortisone confirmed the diagnosis of non-classic congenital adrenal hyperplasia. Conclusion: Early diagnosis and therapy enable a better quality of life, reaching the target height in adulthood and avoiding the development of complications.